Analisis Kinerja Keuangan PT. PLN Tahun 2010-2017 - Irsan; Masnoni; Lia Sari; Kemas Welly Angga Permana; Roy Saleh (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This study aims to analyze financial performance of PT. PLN during 2010 till 2017. Financial performance to be analyzed is the performance of liquidity and solvency. Data obtained from the financial statements of PT. PLN during 2010 to 2017. Researchers isolate the effect of asset revaluation conducted by PT.PLN in 2015. Analysisis carried out using liquidity ratiosand solvency ratios.The liquidity ratiouses the currentratioandcash ratio,while the solvency ratiouses the DebttoEquity Ratio, Debt Ratio, and Times Interest Earned Ratio.The analysis shows that the current ratio fluctuates only in the range of 0.24 to 0.36 while the fluctuating cashratiois only inthe range of 0.06 to 0.15.During the observation period for 8years PT.PLN experiences illiquid conditions. The debt to equity ratio is only fluctuating in the range of 1.47 to 2.93. The fluctuating debt ratio is in the range of 0.59 to 0.75. The fluctuating TIE ratio is in the range of 1.21 to 2.21.D uring the observation period for 8 years PT. PLN experiences in solvency conditions. This condition shows that PT.PLN faces highrisk financial.